One-sided complements and solutions of the equation aXb=c in semirings - Sam L. Blyumin; Jonathan S. Golan (International Journal of Mathematics and Mathematical Sciences)
Given multiplicatively-regular elements a and b in a semiring R, and given an element c of R, we find a complete set of solutions to the equation aXb=c. This result is then extended to equations over matrix semirings.